The lack of structure of knowledge - Lopes, Arthur Viana (Aufklärung: journal of philosophy, 2018)
For a long time philosophers have struggled to reach a definition of knowledge that is fully satisfactory from an intuitive standard. However, what could be so fuzzy about the concept of knowledge that it makes our intuitions to not obviously support a single analysis? One particular approach from a naturalistic perspective treats this question from the point of view of the psychology of concepts. According to it, this failure is explained by the structure of our folk concept of knowledge, which organizes its constitutive information in a much looser way than we assume when we rely on intuitive knowledge ascriptions. I will adopt the same starting point here, but argue against the proposed answer and defend the view that this difficulty is explained not by something related to the specific structure of our concept of knowledge but, on the contrary, by its lack of structure. I claim that our folk concept of knowledge should be understood as a primitive mental state concept.